May Measurement Month 2017: analysis of the blood pressure screening results in Ecuador—Americas. (24th April 2019) - Peñaherrera, Ernesto; Ramirez, Maria; Peñaherrera, Ruben; Mora, Cecilia; Duarte, Yan; H. Del Brutto, Oscar; Jarrin, Estefania; Avila, Elisa; Ruales, Jose; Vintimilla, Juan; Arteaga, Fabricio; Beaney, Thomas; et al.
Abstract: Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. Previous hypertension surveys in Ecuador, showed that there was a prevalence of 28% of adults with hypertension in 1999, 53% in adults between 60 and 75 years in 2010, and. 9.3% in people between 18 and 59 years in 2012 [Freire WB, Ramírez-Luzuriaga MJ, Belmont P, Mendieta MJ, Silva-Jaramillo MK, Romero N, Sáenz K, Piñeiros P, Gómez LF, Monge R. Tomo I: Encuesta Nacional de Salud y Nutrición de la población ecuatoriana de cero a 59 años. ENSANUT-ECU 2012. Ministerio de Salud Pública/Instituto Nacional de Estadísticas y Censos. Quito-Ecuador 2014]. The May Measurement Month (MMM) is a global initiative aimed at raising awareness of high BP that can temporarily address the lack of screening programmes worldwide. Verbal informed consent was obtained from respondents. We enrolled 16 sites for the measurement of arterial BP and completion of the MMM17 questionnaire, the most important sites being: Guayaquil, Quito, Cuenca, Milagro, Esmeraldas, Duran, Naranjito, and Machala. We administered the MMM17 survey on 6984 people, of which 50.5% of them were men and 48.4% were women. Mean age was 46.62 ± 17.71 SD. The crude mean BP was 115/74 mmHg. Of the 6984 people who completed the survey, we had 1522 that were already taking anti-hypertensive treatment. The number of people with hypertension (≥140 or ≥90 or on treatment for hypertension) was 1968/6982 (28.2%) persons. The number of people with hypertension of those not receiving treatment was 446/5460 (8.2%) and the number of people receiving treatment but with controlled and uncontrolled BP was 1136/1522 (74.6%) and 386/1522 (25.4%), respectively. MMM17 was the largest BP screening campaign undertaken in Ecuador. We identified 446 people with hypertension that were not receiving any treatment and 386 people with uncontrolled hypertension. These results suggest that opportunistic screening can identify significant numbers with raised BP.